Growth and mortality of the triggerfish Canthidermis sufflamen (Perciformes: Balistidae) from Los Frailes and Los Testigos Archipelagos, Venezuela - Alarcon, Mayra Jennifer (2017)
Canthidermis sufflamen has become a low cost food resource in high demand in El Tirano fishing community, and captures have been increasing in recent years. Since there is a lack of information on this resource population dynamics in Venezuela, the goal of this research was to provide some biological-fishery parameters, and has as general objective to determine growth and mortality of the triggerfish of Los Frailes and Los Testigos Archipelagos, Federal Territories of Venezuela. For this, a total of 3 595 specimens were collected from El Tirano commercial fishing, every week, from May 2012 to April 2013. We determined total length (cm), total weight (g), and sex for each specimen. No sexual dimorphism was shown with respect to length (ts = -0.96; p > 0.05), so one length-weight ratio was established for both sexes: W = 0.164*L2.26;and they both exhibited minor allometric growth. Growth was estimated by analysis of the frequency distribution of lengths, using FiSAT software. Growth parameters, estimated by the von Bertalanffy model, were considered slow, being L∞ = 61.69 cm, W∞ = 1 868.40 g, k = 0.36 / year, and to = -0.65 years. The maximum age was A0.95 = 8 years. The growth index (Ø′), showed a value of 3.14. The exploitation rate E = 0.72 / year, using total mortality values Z = 2.67 / year, natural M = 0.73 / year and from fishing F = 1.93 / year, indicates that C. sufflamen is being over-exploited by the artisanal fishers of El Tirano. We recommend following some harvest guidelines that will reduce mortality rate due to fishing.